Efficacy of probiotics on growth performance and hemato-biochemical parameters in broiler (Research in Agriculture Livestock and Fisheries, 2019)
Cobb-500 broiler chicks were used to study the effects of probiotics on growth performances and haemato-biochemical parameters. A total of fifteen broiler chicks (16 days old) were randomly divided into three equal groups (n=5). Two groups of broilers were fed probiotics at the rate of 0.5 gm/kg and 1gm/kg respectively with commercial feed for 22 days. Chicks fed on only commercial feed were considered as control group. The results showed that broilers treated with probiotics grew faster compared to control group. After having completed the trial, the birds were sacrificed to collect blood sample for hematological and biochemical analysis. Dressed weight, weight of skin including feathers, leg weight, breast weight and liver weight were found higher in treated groups compared to control group. Total erythrocytes count and hemoglobin content were found increased in treated group compared to control group. ESR value was found decrease in treated groups compared to control group. Total cholesterol, triglycerides and HDL was significantly (P>0.01) lower in the treated groups compared to control group. The serum alkaline phosphatase significantly (P